#TITLE_ALTERNATIVE# - ARIZKI (NIM: 20515048), MUHAMAD
Caged-FRET (caged Förster-Resonance Energy Transfer) is a proven method that can be used to improve imaging-based biological research by using a prequenched or photoswitchable fluorophores. Reversible quenching of certain fluorophores can be done using reductive caging by certain reductive agents, such as tris(2-carboxyethyl)phosphine and sodium borohydrate. Specific reduction reaction was used to deactivate organic fluorophores which then can be reactivated using light at ultraviolet wavelengths. This principle can be applied to enhance the range of experiment in smFRET (single-molecule Förster-Resonance Energy Transfer) field. This study was conducted to prove that caging and/or UVreactivation can be combined with smFRET-based analysis using confocal microscopy to improve the obtained information so that the analysis of complex biochemical species can be done in easier ways. It has been shown that reactivation of photoswitchable rhodamine fluorophores (cage552) and sequentially caging and reactivation of cyanine fluorophores (cy5) on the synthetic nucleic acid containing more than two fluorescence label, can generate additional information that was not originally obtained when the ALEX-smFRET (alternating laser excitation-smFRET) experiment was conducted in the absence of caging and/or reactivation. In addition, removal of unwanted species of multisubunit protein, BetP S516C, which was labeled in each of its subunit was undertaken in two steps. The first one was by varying the labeling ratio with optimum ratio of 2:5. The resulted labeled protein was then quenched by TCEP to completely eliminate the unwanted species, followed by measurement using ALEX-smFRET technique. The optimum condition for BetP S516C measurement was found to be at pH 9 with 1.5 mM of TCEP for 2 hours incubation.